A brief report on the March 21, 2019 explosions at a chemical factory in Xiangshui, China. Issue 2 (11th May 2019) - Zhang, Nan; Shen, Shui‐Long; Zhou, An‐Nan; Chen, Jun
Abstract: This short communication reports on a catastrophic explosion which occurred on March 21, 2019 in Xiangshui County, Jiangsu Province, China. The huge explosion resulted in the death of 78 people and the injury of 617. The causes of this accident are analyzed following reporting of the background, explosion scenes, and rescue operation of the accident. Based on the preliminary investigation, some measures to prevent similar accidents are suggested.